Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/nn1739
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular proteins exocytosed and subsequently retrieved by compensatory endocytosis are nonidentical

Abstract: Upon exocytosis, synaptic vesicle proteins are released into the plasma membrane and have to be retrieved by compensatory endocytosis. When green fluorescent protein-labeled versions of the vesicle proteins synaptobrevin-2 and synaptotagmin-1 are overexpressed in rat hippocampal neurons, up to 30% are found on axonal membranes under resting conditions. To test whether and to what extent these plasma membrane-stranded proteins participate in exo-endocytic cycling, a new proteolytic approach was used to visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
299
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(327 citation statements)
references
References 49 publications
(60 reference statements)
27
299
1
Order By: Relevance
“…1 A-C). Although a considerable fraction of the sybII constructs is localized in the plasma membrane as expected (18) and generates diffuse fluorescence, punctate fluorescence is clearly visible, indicating vesicular localization. Further evidence for vesicular localization comes from observation of vesicular movement (Movies S1-S3).…”
Section: Resultsmentioning
confidence: 53%
“…1 A-C). Although a considerable fraction of the sybII constructs is localized in the plasma membrane as expected (18) and generates diffuse fluorescence, punctate fluorescence is clearly visible, indicating vesicular localization. Further evidence for vesicular localization comes from observation of vesicular movement (Movies S1-S3).…”
Section: Resultsmentioning
confidence: 53%
“…Two recent studies found evidence for the existence of a pool of synaptic vesicle proteins on the plasma membrane that is selectively and readily retrieved after brief or mild stimuli (49,50). Partially preassembled endocytic structures waiting to be recovered after a stimulus could, in principle, account for the rapid endocytosis elicited under some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are mobile and intermix with newly exocytosed synaptic vesicle proteins 44,45 . By contrast, super-resolution stimulated emission depletion (STED) microscopy (BOX 4) has suggested that newly exocytosed synaptic vesicle proteins are clustered at the plasma membrane 46 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…This apparent contradiction could be explained by differences between pHluorin-tagged synaptic vesicle membrane proteins and their native endogenous counterparts 47 . Alternatively, synaptic vesicle proteins may undergo postexocytic reclustering within the periactive zone 44,45 (FIG. 4), a process that could become rate-limiting under conditions of sustained activity (see below).…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
See 1 more Smart Citation